2021
DOI: 10.1093/brain/awab132
|View full text |Cite
|
Sign up to set email alerts
|

Deep grey matter injury in multiple sclerosis: a NAIMS consensus statement

Abstract: Although multiple sclerosis (MS) has traditionally been considered a white matter disease, extensive research documents the presence and importance of gray matter injury including cortical and deep regions. The deep gray matter (DGM) exhibits a broad range of pathology and is uniquely suited to study the mechanisms and clinical relevance of tissue injury in MS using magnetic resonance techniques. DGM injury has been associated with clinical and cognitive disability. Recently, MRI characterization of DGM proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 115 publications
2
37
0
1
Order By: Relevance
“…The importance of subcortical neurodegeneration in MS has been recently summarised by Ontaneda et al (2021), emphasising that atrophy of deep GM structures is common in MS and may be a suitable target for DMT treatment [62]. In this study, we observed prominent subcortical volume change in early RRMS, which is in line with previous studies reporting early-stage subcortical atrophy, specifically in the thalamus and basal ganglia [14, 19, 24].…”
Section: Discussionsupporting
confidence: 91%
“…The importance of subcortical neurodegeneration in MS has been recently summarised by Ontaneda et al (2021), emphasising that atrophy of deep GM structures is common in MS and may be a suitable target for DMT treatment [62]. In this study, we observed prominent subcortical volume change in early RRMS, which is in line with previous studies reporting early-stage subcortical atrophy, specifically in the thalamus and basal ganglia [14, 19, 24].…”
Section: Discussionsupporting
confidence: 91%
“…This occurs in 40% to 65% of MS patients across all phenotypic classifications (Rao et al, 1991) and frequently overlaps with other clinical variables such as fatigue (Hanken et al, 2014; Takeda et al, 2021) and depression (Niino et al, 2014; Takeda et al, 2021). As MS progresses, multifocal white matter (WM) damage ranging from demyelination to axonal loss may result in disconnection between cortical and subcortical grey matter (GM) areas, involving key structures for cognitive and memory processes even early in the disease course (Dineen et al, 2009; Ontaneda et al, 2021). The limbic system includes crucial WM and GM regions that are involved in aspects of emotions and cognition (Aggleton & Brown, 1999; Thomas et al, 2011), such as the fornix, which is the major efferent WM pathway from the hippocampus with indirect connections to the thalamic nuclei (Raslau et al, 2015; Thomas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The authors did not find a statistically significant increase in annualized subcortical gray matter volume loss, using the freely available FreeSurfer (Charleston, MA, USA) analytical software, in the MS patients with NEDA-3, as compared with an age-and gender-matched control group (n = 61) without neurological or psychiatric disease (controls had a longer radiological interval; 42 months on average), whereas the opposite was true for the MS patients with EDA [19]. Tissue-specific BVL, particularly involving the thalamus [20], has developed as a valuable marker and prognosticator of clinical MS severity but we provide the advantage of presenting whole brain volume data since, overall, global brain volume changes still seem to be more strongly associated with clinical outcome measures than regional estimates [4]. In addition, icobrain ms is one of the three quantification packages cleared by both the European Medicines Agency and the United States Food and Drug Administration and currently the sole application that has been independently validated for purposes related to MS [21].…”
Section: Discussionmentioning
confidence: 99%